(untitled) (International journal of medical sciences, 2026)
In the modern education system, improving teaching methods and ensuring students' active participation in the learning process are urgent issues. Interactive teaching methods play an important role in this regard. Through them, students not only acquire knowledge, but also develop skills such as independent thinking, problem solving, and teamwork.